Adat perkahwinan masyarakat Tamil Sri Lanka Malaysia - Sri Visaladchy, a/p A. Nantha Kumar. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Marriage ceremonies are different between every ethnic group in Malaysia. The same goes with the Malaysian Sri Lankan Tamil. Though, the present generations are not interested wi th the traditional ceremonies and rituals. Due to that, this research is to educate the younger generation, especially the Malaysian Sri Lankan Tamil about the importance of the ceremonies and rituals that is been practiced.